Extreme weather and low-income household finance: Evidence from payday loans - Shihan Xie; Victoria Wenxin Xie; Xu Zhang (Bank of Canada, 2024)
This paper explores the impact of extreme weather exposures on the financial outcomes of low-income households. Using a novel dataset comprising individual-level payday loan applications and loan-level information, we find that extreme temperature days-both hot and cold-lead to surges in demand for payday loans. An increase in the number of days with extreme heat results in an increase in delinquency and default rates and a reduction of total credit issued, indicating a contraction in loan supply. These effects are especially noticeable for online payday loans. Our findings highlight the heightened financial vulnerability of low-income households to environmental shocks and underscore the need for targeted policies.
Keywords: Q54; G50; 330; Climate change; Credit and credit aggregates